Experimental modelling of hydraulic parameters for fluid flow in stratified porous media. Issue 1 (31st December 2023) - Alabi, O.O.; Akanni, I.A.; Sedara, S.O.
Abstract: From works in in-situ seepage through dams and laboratory experiments using Layered Heterogeneous Porous Media (LHPM), it has been noted that a refraction-like phenomenon, such as that experienced in light, affects fluids' flowlines when crossing the contact interface of layers characterised by different porosity viz-a-viz permeability. This concept has many applications in fluid dynamics, such as the dispersion process in stratified media. Currently, no study exists that models and analyses the relationship between the porosities of two layers in contact and the resulting flowline refraction using validated LHPM data. Hence, this work aims to establish a relationship between the porosity ratio Φ r of stratified media made up of two layers and the refraction angle θ m a x of the maximum volume flux q m a x . Volume flux data from the flow of a single-phase fluid through five LHPMs with Φ r ranging from 0.8325 to 0.9524 were used in the modelling. The flow was oriented from the lower to the higher porosity vis-à-vis permeability layer. It was found that θ m a x which is also the refraction angle of the peak solute plume flux, refracts away from the normal as Φ r reduces. This indicates an increase in the dilution rate vis-à-vis spread of plumes with the reduction in homogeneity between the two layers. Also, θ m a x does not correlate with the stratification inclination α, but the q m a x which is also the peak solute plume flux correlates with α . Furthermore, an efficient model, which is the best-unbiased estimator, with R 2 = 0.99 was derived. Findings from this work can help better understand solute plume dispersion and the general fluid flow dynamics in stratified media such as capillary barrier effect covers for pollution control and hydrocarbon reservoirs.